Differences of Mathematics Learning Results between Make a Match Cooperative Methods and Expository Methods - Otto Fajarianto; Nailah Tresnawati; Tri Candra Wulandari; Andy Ahmad (EDUTEC : Journal of Education And Technology, 2022)
Mathematics is a branch of science that is always used in all life and also supports other sciences. Learning outcomes in learning are very important because the success of learning carried out in teaching and learning activities can be seen from student learning outcomes. Learning outcomes are the results achieved by students or someone after doing learning activities. teachers must find the right method in learning mathematics. Difficulty and low interest of students in learning and understanding mathematics material can be overcome by applying appropriate learning methods. The purpose of this study was to determine the differences in student learning outcomes taught through the Make A Match type cooperative learning method and the expository method on triangular flat shapes. From the observations seen from student learning activities, it shows that the more active and more enthusiastic in learning are the classes that use the Make A Match learning method. This means that the Make A Match learning method has better learning outcomes than the Expository learning method.